Seasonal variation of fatty acid profile in edible tissue of deep-sea whip lobster Puerulus sewelli (Decapoda, Palinuridae) - Chakraborty, Kajal; KRISHNAN, SOUMYA; CHAKRABORTY, REKHA DEVI; MANI, ASWATHY ELIZABETH; VIJAYAGOPAL, P. (Indian Journal of Fisheries, 2022)
Seasonal variations of the fatty acid profile of deep-sea whip lobster Puerulus sewelli (Decapoda, Palinuridae), harvested from the south-west coast of India were compared. Fatty acid contents showed seasonal fluctuations, with eicosapentaenoic acid and docosahexaenoic acid being predominant during the post-monsoon and winter seasons (9-11% of cumulative fatty acids). P. sewelli was found to possess considerably higher C20-22 n-3 fatty acids during these seasons along with balanced n-3/n-6 (>2) and polyunsaturated/saturated fatty acid ratio (≥1) than those in pre-monsoon. Greater hypocholesterolemic/ hypercholesterolemic ratio (>2.4) and lesser atherogenicity (<1.8) and thrombogenicity (<0.3) indices qualify P. sewelli an ideal health food. This study comprises the first report on fatty acid profile from commercially important deep-sea whip lobster P. sewelli. Keywords: Atherogenicity index, Non-conventional resource, Polyunsaturated fatty acid, Seafood benefits, Thrombogenicity index